Nitrogen mineralization from organic amendments predicted by laboratory and field incubations - Pinto, Rui (2020)
Reliable methods to estimate nitrogen (N) mineralization from organic amendments are needed to improve the fertilization recommendations for organic horticultural crops. With this aim, N mineralization from farmyard manure compost (FYMC), commercial organic fertilizer (COF) based on materials that are prompt to rapid N mineralization and green manure was determined in field situation where environmental factors affect mineralization rates and under controlled laboratory conditions that may not reflect conditions in the field. The ability of field and laboratory incubations to predict N mineralization was estimated during a field organic crop rotation set up with a cover crop of rye and vetch, followed by Portuguese cabbage and carrot. The relationship between mineralized N in field incubation and crop N accumulation suggests that field incubation is effective to predict N mineralization from FYMC, COF and green manure. However, the pattern of N mineralization from FYMC and green manure was different in field and laboratory incubation conditions as opposed to N mineralization from COF that was similar in both incubations. © 2020, © 2020 Taylor & Francis Group, LLC.